Family communication and its role in awareness of the dangers of electronic games (A field study on a sample of students' parents in the city of Laghouat) - Sidahmed BENLAHBIB; Abdennabi ZENDRI (Social Sciences Journal, 2021)
Our study is part of the studies that try to determine the relationship between the variables, as our study included the independent variable, which is family contact and the dependent variable, which is electronic games, where we tried to stand or understand the real relationship that exists between the two variables, and to reach the real role that the family plays in reducing risks Electronic games, as the latter has become a major influence on the minds of children as it has affected the customs and traditions of the family, and this is what we noticed through the study that we carried out on the level of parents of some middle school students in the state of laghouat, in which we observed that students dealt with such games significantly.